Pancasila sebagai Ideologi Negara: Kehidupan Berbangsa dan Bernegara : Penelitian - Fitriyah; Raka Syukur; Z Slam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to examine and analyze the meaning and role of Pancasila as the state ideology in the life of Indonesian society and nation through a literature review. This study was conducted using various documentary sources, including books on the philosophy of Pancasila, historical documents, and academic articles related to state ideology. The values contained in the five principles of Pancasila have proven to be the foundation for a harmonious, just, and civilized life, even amid ethnic, religious, and cultural diversity. However, challenges such as globalization, modernization, and socio-political changes demand a stronger internalization of Pancasila values. This ensures that these values do not merely serve as symbols, but as concrete guidelines in shaping policies and citizen behavior. This study emphasizes that the process of understanding through examples, education, and public practices rooted in Pancasila values is a strategic step to strengthen national unity and the sovereignty of the Indonesian state.